ISLAM DAN HAK ASASI MANUSIA - Ahmad Gun Gun Fariq; Alpiyatunnur’aliyah, Arip Rahmat Nurhidayat (CV. Adiba Aisha Amira, 2025)
Islamic teachings state that life and death are under the control of Allah, and therefore, no human being is allowed to take away the right to life from another person. This writing aims to broaden the knowledge of others about the discussions surrounding the history of human rights in the West, Islam's view of human rights and the conflicts that occur between human rights and Shari'ah. The method used in this research is to use a qualitative approach, by applying the descriptive-analytical method. The results of this study state that there are five main principles of human rights in Islam, including the principle of protection of religion, soul, mind, offspring, and property. One of the reasons for the conflict between shari'ah and human rights is that Islamic laws are only understood by the majority of the population. Islamic laws are only understood by the majority of the Muslim community, while human rights are understood by all human beings globally, regardless of their religion